Lahirnya Norma Baru Dalam Pengujian Undang-Undang Terhadap Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Oleh Mahkamah Konstitusi - Dwi Putri Cahyawati; Ahmad Azharil (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
Abstract:The Constitutional Court in its position as guardian of the constitution has the authority to examine laws against the Constitution. The position of the Constitutional Court is only limited to negative legislature. However, in its implementation many Constitutional Court decisions sometimes make positive legislature decisions. This has become a debate among observers of state administration law. This research method uses a normative juridical legal research approach, while the type of research used is descriptive qualitative analytical, and data collection techniques are library research. From this research it is known that the constitutional court has raised new norms in judicial review.Keywords: New Norms, Laws, Constitutional Court